Distribution of radionuclides in the soils and assessment of radiation hazards in AL Najaf, Iraq: A cross sectional analysis - Shaymaa Awad Kadhim; Wafaa Jasim; Shatha Alhous (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate radioactivity levels in soil samples and their physical impact on the population. Method: The experimental radiation study was conducted by researchers belonging to the Kufa University in Al-Najaf, Iraq, in August 2020, and comprised soil samples from Al-Rahma area. Sodium iodide detector activated with a trace amount of Thallium with crystal dimensions 3" x 3" was used to calculate the concentration of Radium, Thorium and Potassium. Results: Among the 15 samples collected, the average ± standard deviation (SD) concentration for Radium, Thorium and Potassium was 0.1776±0.12, 0.726±0.435 and 1.9128±1.105%, Respectively. The reported value of excess lifetime cancer risk was 1.2819×10-3. Conclusion: The area studied was found to be a safe area and did not pose a health threat to the locals. Key Words: Thorium, Radium, Sodium Iodide, Thallium, Radioactivity, Neoplasms, Soil